Kepemilikan CEO Dalam Hubungan Antara Kebijakan Utang Dan Kebijakan Dividen - Amrie Firmansyah; Agung Dinarjito; Sondy Akbar Ardiansyah; Rozano Fikri Andana (JAS (Jurnal Akuntansi Syariah), 2022)
This research aims to show the effect of debt policy on dividend policy and the moderating role of chief executive officer (CEO) share ownership in the relationship between debt policy and dividend policy. Data on the financial reports of companies in the non-financial sector listed on the Indonesia Stock Exchange from 2008 to 2020 are used as research data. Research data is sourced from www.idnfinancials.com and the company's official website. The number of samples used in testing this research was 454 observations based on purposive sampling. Data analysis in this research used logistic regression. This research shows the results that debt policy has a negative effect on dividend policy. In addition, CEO share ownership weakens the negative effect of debt policy on dividend policy. This research shows that the Indonesian Financial Services Authority needs to improve governance, especially concerning investment protection on the Indonesian Stock Exchange.